Blockade of monocyte-endothelial trafficking by transduced Tat-superoxide dismutase protein - PARK, SIN-HYE (Int J Mol Med, 2016)
It has previously been suggested that reactive oxygen species (ROS) are involved in the pathogenesis of chronic inflammatory diseases, which entails the initial activation of pro-inflammatory cytokines to facilitate leukocyte transmigration. The present study investigated whether intracellular superoxide dismutase (SOD) suppressed monocyte endothelial trafficking and transmigration. Human umbilical vein endothelial cells (HUVECs) and THP-1 monocytes were activated by the cytokine tumor necrosis factor-α (TNF-α) in the absence and presence of cell-permeable transactivator of transcription (Tat)-SOD protein. External stimulation with SOD was conducted using endothelial cells and monocytes. Purified cell-permeable Tat-SOD, but not non-targeted SOD, at 1–3 µM was transduced into endothelial cells in a time- and dose-dependent manner. Non-toxic Tat-SOD at ≤0.5 µM, but not 1 µM SOD, blocked the monocyte-endothelium interactions by inhibiting the TNF-α-induced stimulation of vascular cell adhesion molecule-1 (VCAM-1) in HUVECs and integrin β1 in THP-1 cells. Endothelial VCAM-1 induction by TNF-α was responsible for superoxide anion production being quenched by N-acetyl-cysteine and Tat-SOD. SOD treatment markedly inhibited superoxide anion production induced by TNF-α, but no inhibition of endothelial transmigration was noted. Tat-SOD prevented transendothelial monocyte migration by firmly localizing occludin-1, platelet/endothelial cell adhesion molecule-1 (PECAM-1) and vascular endothelial-cadherin present in paracellular junctions and inhibiting endothelial induction and activation of matrix-degrading membrane type-1 (MT-1) matrix metalloproteinase (MMP), MMP-2 and MMP-9. By contrast, treatment with 1 µM SOD did not have such effects. Furthermore, transduced Tat-SOD hindered nuclear transactivation of nuclear factor-κB (NF-κB), modulating the induction of paracellular junction proteins and matrix-degrading MMP in TNF-α-stimulated HUVECs. Transduced Tat-SOD, but not external SOD, impeded cytokine-induced endothelial adhesion and the transmigration of monocytes. Thus, we suggest that transduced Tat-SOD qualifies as an atheroprotective agent against oxidation-driven and inflammation-associated atherosclerosis.